Molecular characterization of Infectious Bursal Disease virus from gamefowls in selected areas in CALABARZON, Philippines - Caceres Abbegaile B DVM; Umali Dennis V DVM, PhD; Bernardo Francis Andrew Eugene M DVM, MS; Katoh Hiromitsu DVM, PhD (International Journal of Life Sciences, 2017)
Infectious Bursal Disease (IBD) is a highly infectious, economically important, immunosuppressive viral disease of poultry. In this study, four field strains of IBD virus (IBDV) from gamefowls in selected areas in CALABARZON, Philippines were characterized. Clinical signs observed in affected chickens were inappetence, white scours, ruffled feathers, lethargy and acute increased in mortalities. Gross lesions observed were enlarged hemorrhagic cream colored bursae with yellowish exudates. Hemorrhages in the junction of the proventriculus and gizzard were also noted. Nucleotide sequencing showed that the field strains belong to serotype-1 with deduced amino acid sequences of 222A, 256I, 294I, 242I and 299S at the VP-2 gene, which indicates that the field strains were from the very virulent IBDV (vvIBDV) genotype. Phylogenetic analysis showed that the field strains belong to the European-like vvIBDV subgenotype and were closely related to (97-98%) to Spanish, South African and Nigerian IBDV strains. At present, this is the first molecular characterization of IBDVs in the Philippines.